The relevant of hydroponic system in our country toward customer perspective / Nur Mahsuri Md.Zamri - Md.Zamri, Nur Mahsuri (Faculty of Business and Management, 2009)
This report examines the issue The Relevant of Hydroponic System in Our Country toward the Customer Perspectives. Hydroponics (from the Greek words hydro water and ponos labor) is a method of growing plants using mineral nutrient solutions, without soil. Terrestrial plants may be grown with their roots in the mineral nutrient solution only or in an inert medium, such as perlite, gravel, or mineral wool. The overall objective of this study was to investigate the relevant of hydroponic system in our country toward the customer’s perspective. Kazzponic Sdn.Bhd. should do to improve their selling on their product and is reflected in both their brand and values to maintain the sell of the product. The relevant of hydroponic system in our country can be determined in three categories Economic sustainability and profitability, Environmental concern and Social acceptable. In this study also determine the problem statement is relevant of hydroponic system in our country toward the customer’s perspective. In particular, the company needs to make sure that product it still relevant to market in our country. In order, to get more information about the perception of customers about the relevant of hydroponic in our country the researcher used the research design of Descriptive Research. The researcher used the questionnaire in order to get the information about the research and from the research that shows the hydroponic is still relevant in our country toward the customer perspective. So, as a recommendation’s the company should have implement the effectiveness of advertising and promotion strategy. The companies so do make cooperation with the government in order to agriculture sector and improve their management.